Implementasi Pendidikan Akhlak di Masa Pandemi: Tantangan SMAN 1 Sentajo dalam Menyiapkan Generasi Islami - Ronaldo Rozalino; Riki Saputra; Ahmad Lahmi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
Moral learning has a more specific purpose to form the behavior of learners, therefore the main aspects expected of moral learning are related to attitudes, while for the formation of attitudes require exampleal examples by learners. Learning in the covid-19 period the presence of teachers as figures that are commonly examined by learners' words and actions are very minimal. Therefore, this study wants to reveal how moral learning for students in high school during covid-19. This research was conducted using a quantitative approach, the research sample was a student of Sma Negeri 1 Senta Raya taken with cluster techniques, research data collected with questionnaire techniques. The planning carried out by the teacher has no difference with moral learning planning in normal times. The implementation of learning is done online using the media of the teacher's room. Moral learning outcomes are more dominated by cognitive aspects. This is because the presence of teachers directly is very minimal.